UMP appreciates 68 loyal staff serving for 20 years - Nor Salwana, Mohammad Idris (UMPSA, 2023)
PEKAN, 23 February 2023 - A total of 68 staff of Universiti Malaysia Pahang (UMP) who have faithfully contributed more than two decades of service at this university were celebrated in the Sanjungan Budi Ceremony in conjunction with the Annual Mandate of the UMP Vice-Chancellor 2023 took place at the UMP Multipurpose Hall recently.